Pengaruh Reward dan Motivasi Kerja terhadap Kinerja Karyawan pada PT Aquafarm Nusantara - Liska Febrianti; Marliyah, Marliyah, (LPPM Institut Nasional Laa Roiba Bogor, 2023)
As implemented by PT Aquafarm Nusantara, which offers cash and salary bonuses to workers who meet production goals. The organization's prize framework depends on assessing representative execution, with the expectation that giving honors to all workers will rouse them to work better. PT. Aquafarm Nusantara is a company that raises and cares for fish. Better Normally Tilapia, which is created for homegrown and global business sectors, is the organization's top notch item. PT. Aquafarm Nusantara employs registered representatives from nearby cities in its operations in North Sumatra and Central Java. considering the repercussions of the meeting with HRD that was led by a scientist at PT. Aquafarm Nusantara has various issues, including numerous workers who keep on overlooking organization approaches. as well as the quantity of representatives whose result isn't as per organization objectives. This happened in light of the fact that PT Aquafarm Nusantara representatives didn't grasp the reason for giving approvals and cautioning letters to rouse them to work on their exhibition, and a few workers were careless and believed the approvals and cautioning letters to be minor, bringing about a lessening in the nature of execution. representative execution. Thus, authorizations and admonitions gave by HRD couldn't stop representatives. Scientists are keen on taking the title